2021
DOI: 10.1590/1809-2950/21017028032021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de fragilidade autorreferida em pacientes criticamente enfermos acordados e alertas

Abstract: RESUMO Indivíduos criticamente enfermos internados em unidades de terapia intensiva (UTI) podem apresentar perdas de reservas físicas e cognitivas que aumentam a vulnerabilidade frente a eventos adversos, caracterizando a síndrome da fragilidade. O objetivo do estudo foi delinear a prevalência de fragilidade autorreferida em pacientes criticamente enfermos acordados e alertas internados na UTI de um hospital escola. Foram incluídos indivíduos adultos (≥18 anos), internados por, pelo menos 48 horas nas UTI de u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In the analyzed sample, the frailty that prevailed was mild with 30.8%, In the study by Stortet al, carried out with elderly people hospitalized in a hospital ward and using the same Edmonton Frail Scale (EFS), reporting that 95.2% of the elderly were frail, with a prevalence of severe frailty [13]. While in Galdiano's study et al which aimed to assess awake patients in an Intensive Care Unit ICU and who were able to respond to five simple commands, but used the clinical frailty scale, which has the same objective as the Edmonton frailty escalation; where the prevalence of self-reported frailty was null and the researchers reported that it may have been due to the small sample size [14]. A third study by Freire et al, who searched for some articles in order to better understand the prevalence of frailty in hospitalized elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In the analyzed sample, the frailty that prevailed was mild with 30.8%, In the study by Stortet al, carried out with elderly people hospitalized in a hospital ward and using the same Edmonton Frail Scale (EFS), reporting that 95.2% of the elderly were frail, with a prevalence of severe frailty [13]. While in Galdiano's study et al which aimed to assess awake patients in an Intensive Care Unit ICU and who were able to respond to five simple commands, but used the clinical frailty scale, which has the same objective as the Edmonton frailty escalation; where the prevalence of self-reported frailty was null and the researchers reported that it may have been due to the small sample size [14]. A third study by Freire et al, who searched for some articles in order to better understand the prevalence of frailty in hospitalized elderly.…”
Section: Discussionmentioning
confidence: 99%